Neglected Cervical Facet Dislocation without Neurological Deficit: A Simple Solution to a Complex Problem—A Case Series and Review - Kumar, Vishal; Rai, Ankit; Dhatt, Sarvdeep Singh (Indian Journal of Neurotrauma, 2024)
Cervical facet dislocation is a disastrous injury. Delayed presentation is not uncommon owing to various reasons in developing countries. Autofusion and a halt in progression are seen in spondylolysis and spondylolisthesis. Conservative treatment with close observation can be offered to the carefully selected patients with neglected cervical facet dislocations with intact neurology, as the injury is stable after autofusion. We registered eight male patients with cervical facet dislocation with delayed presentation for various reasons. Dynamic radiographs, computed tomography (CT) scan, and magnetic resonance imaging (MRI) were done to rule out any instability, cord compression, or bony fusion. Patients were followed up for 6 months clinically and radiologically. A total of eight patients presented with cervical facet dislocation, with a mean delay in presentation of 33 weeks (range: 14–54 weeks). Postinjury, all the patients were neurologically intact, with the only complaint of cervical pain at presentation. Dynamic radiographs did not show any instability. No cord compression or changes were noted on the MRI. Conservative management was advised for all eight patients. A subsequent follow-up CT scan demonstrated bony fusion at the dislocated facets in three of these patients. All the patients remained neurologically intact, with no further progression of the deformity. Surgical management is the mainstay of treatment for neglected facet dislocations. A combined approach has been advocated in most of the studies for proper reduction and alignment in these cases, which is quite extensive and has its own morbidity. A trial of conservative treatment can be offered to selected patients with intact neurology.
Keywords: cervical facet dislocation; neglected cervical injury; autofusion; nonsurgical management; delayed presentation